2014
DOI: 10.1363/46e0514
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Types and Contraceptive Use Within Young Adult Dating Relationships

Abstract: Classifying short-term relationships as "casual" or long-term ones as "serious" may ignore heterogeneity within these categories that may have implications for contraceptive use. Future qualitative research could provide a better understanding of relationship types and couples' fertility intentions and access to and use of contraceptives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 33 publications
2
36
0
5
Order By: Relevance
“…Following other work in this area 28 , we believe that this may reflect the inherent challenges and control issues that emerge in the dyadic nature of the practical negotiating of another person’s condom use versus one’s own, which typifies female versus male condom use. Arguably, this may also represent adolescent females’ transition to other forms of protection, particularly in higher intimacy relationships 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Following other work in this area 28 , we believe that this may reflect the inherent challenges and control issues that emerge in the dyadic nature of the practical negotiating of another person’s condom use versus one’s own, which typifies female versus male condom use. Arguably, this may also represent adolescent females’ transition to other forms of protection, particularly in higher intimacy relationships 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Hooking up includes a continuum of physical behaviors including kissing and genital stimulation (in addition to oral, anal, and vaginal sexual intercourse), and choosing not to engage in penile-vaginal penetration is perhaps one way to attempt to avoid pregnancy. Research suggests that the most common method of pregnancy prevention during penile-vaginal intercourse during casual sex is condom use (Manlove et al 2014), but use of highly effective contraception or dualmethod use occurs as well (Walsh et al 2014).…”
Section: Casual Sex and Sexual Healthmentioning
confidence: 99%
“…Fielder et al's (2013) longitudinal study of first year college students suggested that hookup behavior predicted the acquisition of STIs. Perception of risk of acquiring STIs varies based on the type of casual sex (e.g., hook-up versus FWB) (Manlove et al 2014;Pollack et al 2013) and type of physical contact (e.g. oral sex versus vaginal intercourse) (Downing-Matibag and Geisinger 2009;Pollack et al 2013).…”
Section: Casual Sex and Sexual Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of sexually active teenagers find that relationship characteristics, such as age at first sexual encounter [4], relationship type and length [5], level of intimacy [5], communication [6], and partner homogamy [7] are associated with contraceptive use. One national study found that young women’s odds of ever having used contraception in first sexual relationships increased with the relationship duration and decreased if they had not known their partner before dating him.…”
Section: Introductionmentioning
confidence: 99%